Numerical and Experimental Study of a Wing Combined with Wing Grids in Low Reynolds Number Flows - M. sadeghi Malekabadi; A. Banazadeh (مهندسی مکانیک شریف, 2022)
One of the reasons for the increase in induced drag is the vortices created at the wing tip, which has a significant effect on reducing aerodynamic efficiency. Therefore, in order to reduce vortices and the induced drag as well as to improve the aerodynamic performance, the use of wing grid is recommended. Wing grids perform better at low Reynolds numbers, and combination of parameters such as taper ratio, aspect ratio, and twist has a better effect on wing performance and reducing turbulence intensity and induced drag. The purpose of this paper is to improve the aerodynamic performance of compound wing using the wing grids. In this study, the numerical and experimental approaches have been used to investigate the effect of these parameters and also, two key parameters: the grid dihedral angle and sweep angle. Also, a force balance test has been performed for force analysis and numerical solution validation. Wing grid dihedral angle decreases induced drag by increasing the space between separated tip vortices and prevents reinforcing effects due to superposition. On the other hand, dihedral angle should be arranged to increase the aerodynamic efficiency. In other words, increase in dihedral angle may defect the overall performance of the wing. The optimum configuration is found to be symmetric, where the dihedral distribution with a 40° angle for the first grid is reduced gradually to a value of -20° for the last one. In addition, sweep angle distribution for the obtained optimized dihedral angle is also investigated. Initially, each grid span is decreased from the first grid to the last at a constant rate. This increases the sweep angle and enhances the aerodynamic efficiency by 15%. Furthermore, the span of the side grids is reduced from the middle grid and marching the wing leading and trailing edges. Elliptical wing configuration has also been shown to increase aerodynamic efficiency by approximately 50%.